Postoperativni nekrotizirajući fasciitis donjeg ekstremiteta kao neočekivana komplikacija vaskularne hirurgije - prikaz slučaja - Zogić, Enes; Alihodžić, Kemal; Toković, Demir; Nicević, Aldin; Detanac, Džemail (Scripta Medica, 2023)
Necrotising fasciitis is a rare and severe disease, acute infection, often life-threatening, characterised by rapid and progressive spread through the subcutaneous tissue and superficial fascia. It can occur on any part of the body, mostly affecting the perineum, limbs and abdominal wall. A 76-year-old male patient with the development of lower limb necrotising fasciitis after a vascular procedure femoral-popliteal bypass, performed due to chronic ischaemia is presented. Patient previously had several different vascular procedures on other blood vessels, with diabetes and cardiovascular disease as leading comorbidities. Treatment included urgent surgical necrotomy, with all measures of conservative treatment. During the treatment, there was no need for a new vascular procedure, arterial flow was preserved. It is necessary to constantly remind surgeons about this rare but life-threatening disease so that they can recognise it in time and adequately treat it.
Keywords: Nekrotizirajući fasciitis; Teška infekcija; Donji ekstremiteti; Urgentna hirurgija